The use of linseed oil cake in the diets of rohu, Labeo rohita (Hamilton), after solid-state fermentation with a fish gut bacterium, Bacillus pumilus (KF640221): an appraisal on growth, digestibility, body composition, and hematobiochemical profile - Banerjee, Sudeshna; Kari, Zulhisyam Abdul; Téllez-Isaías, Guillermo; Ghosh, Koushik (Frontiers in Marine Science, 2023)
Introduction Linseed or flaxseed (Linum usitassimum L.) contains a prospective source of protein and energy to be utilized in animal feed. This study aimed at re-cycling and value-addition of Linseed Oil Cake (LOC) for formulation of non-conventional carp diets. Methods The LOC was bio-processed through solid state fermentation (SSF) with a fish gut bacterium, Bacillus pumilus (KF640221). Nine experimental sets of diets were formulated using raw (R1-R4) and SSF-processed (F1-F4) LOC at 10%, 20%, 30% and 40% levels substituting fishmeal as well as other ingredients in a reference diet, and rohu, Labeo rohita fingerlings (2.08±0.03 g) were fed for 70 days feeding trial. Growth, carcass composition, activities of digestive enzymes, digestibility and haemato-biochemical parameters were studied following standard methodologies. Results SSF significantly (P< 0.05) improved crude protein along with amino acids, whereas crude fibre and antinutritional factors were reduced considerably. Experimental diets were isocaloric (4.8 kcal) and isonitrogenous (36%). Diets with bio-processed LOC had significantly better performance than the raw LOC. Fish fed diet F3 with 30% fermented LOC resulted in the highest weight gain (6.25 ± 0.09 g), specific growth rate (% day -1) and carcass protein deposition (16.77±0.34%). Activities of the digestive enzymes (amylase, lipase and protease) were also significantly (P<0.05) higher in fish receiving diets containing fermented LOC. Analyses of blood parameters revealed that haemoglobin, erythrocytes, leukocytes, plasma lipid, total plasma protein, albumin and globulin contents were increased, while plasma glutamic-oxaloacetic transaminase (GOT) and glutamic-pyruvic transaminase (GPT) levels were decreased in fish fed bio-processed LOC supplemented diets. Conclusion The present study might propose substitution of fish meal along with other conventional ingredients by incorporation of 30% SSF-processed LOC in the diets of rohu with no negative effect to the growth performance, carcass composition and feed utilization.